2021
DOI: 10.1186/s12890-021-01432-7
|View full text |Cite
|
Sign up to set email alerts
|

Rhomboid intercostal block combined with sub-serratus plane block versus rhomboid intercostal block for postoperative analgesia after video-assisted thoracoscopic surgery: a prospective randomized-controlled trial

Abstract: Background Rhomboid intercostal block (RIB) and Rhomboid intercostal block with sub-serratus plane block (RISS) are the two types of plane blocks used for postoperative analgesia after video-assisted thoracoscopic surgery (VATS). This prospective randomized controlled trial was performed to analyze the postoperative analgesic effects of ultrasound-guided RIB block and RISS block after video-assisted thoracoscopic surgery. Methods Ninety patients ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 21 publications
0
40
0
Order By: Relevance
“…We used data from several secondary analyses of these studies in this meta-analysis. A total of 216 patients were enrolled in 4 included studies [15][16][17][18] , 108 in the RIB group, 108 in the control group with no blocks. The strategy of the research and the process of the selection were shown in the ow diagram of Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We used data from several secondary analyses of these studies in this meta-analysis. A total of 216 patients were enrolled in 4 included studies [15][16][17][18] , 108 in the RIB group, 108 in the control group with no blocks. The strategy of the research and the process of the selection were shown in the ow diagram of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1. All 4 [15][16][17][18] studies were randomised controlled trials published in peer reviewed journals. Two trials 17,18 compared RIB with no block.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations